Imported insecticide resistance in diamondback moth - Voice, D.G.; Chapman, R.B. (New Zealand Plant Protection, 2000)
Laboratory experiments were conducted to determine whether resistance in an Australian population of diamondback moth could be conferred to a local susceptible population of diamondback moth (Plutella xylostella) Bioassays with larvae showed a 715fold difference in response at the LC50 to alphacypermethrin between the resistant imported and local susceptible populations The response of a hybrid strain from these populations displayed a lower level of resistance and a backcross of hybrids with the parents an even lower level of resistance The hybrid strain did not suffer any fitness disadvantage when compared with the parents